Efficient White‐Light Generation from Ionically Self‐Assembled Triply‐Fluorescent Organic Nanoparticles. Issue 26 (24th May 2016) - Das, Susmita; Debnath, Tanay; Basu, Amrita; Ghosh, Deepanwita; Das, Abhijit Kumar; Baker, Gary A.; Patra, Amitava
Abstract: Low cost, simple, and environmentally friendly strategies for white‐light generation which do not require rare‐earth phosphors or other toxic or elementally scare species remain an essentially unmet challenge. Progress in the area of all‐organic approaches is highly sought, single molecular systems remaining a particular challenge. Taking inspiration from the designer nature of ionic‐liquid chemistry, we now introduce a new strategy toward white‐light emission based on the facile generation of nanoparticles comprising three different fluorophores assembled in a well‐defined stoichiometry purely through electrostatic interactions. The building blocks consist of the fluorophores aminopyrene, fluorescein, and rhodamine 6G which represent blue, green, and red‐emitting species, respectively. Spherical nanoparticles 16(±5) nm in size were prepared which display bright white‐light emission with high fluorescence quantum efficiency (26 %) and color coordinate at (0.29, 0.38) which lie in close proximity to pure white light (0.33, 0.33). It is noteworthy that this same fluorophore mixture in free solution yields only blue emission. Density functional theory calculations reveal H‐bond and ground‐state proton transfer mediated absolute non‐parallel orientation of the constituent units which result in frustrated energy transfer, giving rise to emission from the individual centers and concomitant white‐light emission. Abstract : The light fantastic : Intramolecular proton transfer and frustrated energy transfer induced intense white‐light emission from a triply fluorescent organic nanoparticle (see figure).